Analysis of Mandailing Language Interference in Indonesian - Daulay, Mayrani (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
This research aims to determine Mandailing Language Interference with Indonesian. In this research, of course, there is a research method used, and the method used by researchers in analyzing Mandailing Language Interference with Indonesian is a descriptive method and the data analyzed is in the form of qualitative data. After having a method, of course this research is a conversation piece from the Padang Lawas Youth Association, and the end of the research is the research results. The research results from this research are that the interference used is in the field of Indonesian morphology in the use of the Mandailing language which can be seen in the morphological process which includes the process. affixation. This morphological interference includes the interference of the prefixes di-, ter- , ke -, N-, pa-, and sa-; suffix interference –an; confix interference includes ke-/-an, N/-i, N-/- ake, di-/-i, di-/-ake, pa-/-an, and ka-/-an; and the combined affix interference meN-(per-ake) and di-(per-/-ake). Those that are often used are prefixes and surfixations, while those that are rarely used are infixation and confixation. Keywords: interference analysis, Mandailing language, Indonesian